Problems in hand surgery: solutions to recover function - Neumeister, Michael W.; Sauerbier, Michael (Thieme, 2020)
"The intricate balance of the intrinsic and extrinsic soft tissue structure and boney scaffold of the hand, coupled with 31 articulating services in the hand and wrist can lead to significant surgical challenges. Providing surgeons with technical pearls to overcome these challenges is the primary focus of Problems in Hand Surgery by internationally renowned hand surgeons Michael W. Neumeister, Michael Sauerbier, and an impressive group of contributors. Organized by 29 sections and 90 chapters, this comprehensive book focuses on secondary hand surgeries to optimize hand form and function in patients with challenging trauma- and disorder-related hand issues. Among the many topics addressed are problems associated with nonunion, malunion, dysvascular limbs, trauma-related degenerative changes, stiffness, tendon dysfunction, joint disruption, nerve injury, neuropathy, vasospasm, fractures, and osteoarthritis".
Literaturangaben
Auf dem Umschlag: + Online at MedOne, Videos
Keywords: Aufsatzsammlung; Handchirurgie